Advancing access to Medicare‐funded mental health treatment during the opioid epidemic: A counselor advocacy analysis. (14th June 2022) - Westcott, Jordan B.; Fullen, Matthew C.; Jordan, Justin
Abstract: Although advocacy is a priority for counseling professionals, little is known about counseling advocates' participation in the legislative advocacy process. Recent legislation to address the opioid crisis allowed counseling advocates to provide public comments to advance counselor inclusion in the Medicare program. A thematic analysis of 548 public comments provided on behalf of the counseling profession yielded four categories: advocacy on behalf of (1) the proposed rule change; (2) broader Medicare inclusion; (3) the proposed rule change with an additional request for broader Medicare reimbursement; and (4) no clear advocacy. Subthemes included increasing access to care, qualifications necessary to provide care, and the urgency of the opioid epidemic, among others. Implications for the counseling profession and counselor advocacy are discussed.